Peningkatan Kemampuan Membaca Al-Qur'an di Taman Pendidikan Qur’an (TPQ) As-Syakirin Desa Nibung Kecamatan Selimbau Kabupaten Kapuas Hulu - Agus Salim; Rakhmad Putra; Sarmila Sarmila; Marshella Zalianti; Ahmad Dandi; Sri Rezeki Muriati; Ratih Juliandari; Hamisah Hamisah; Rasti Mawarni; Diah Ramada Yanti (Pelayanan Unggulan : Jurnal Pengabdian Masyarakat Terapan, 2026)
The ability to read the Qur’an is a fundamental competence in Islamic education. However, many children still face difficulties in reading the Qur’an accurately and fluently in accordance with tajwid rules. This community service program (Pengabdian kepada Masyarakat/PKM) aimed to improve Qur’anic reading skills of students at Asy-Syakirin Qur’anic Learning Center (TPQ) in Nibung Village, Kapuas Hulu Regency, West Kalimantan. The program employed a Participatory Action Research (PAR) approach, actively involving teachers and students in all stages of the activities. The implementation consisted of planning, action, observation, and reflection stages. During the planning phase, students’ initial reading abilities were identified and grouped into basic (iqra’) and advanced (tahsin) levels, appropriate learning methods were selected, and supporting learning media were prepared. The action phase involved individual and small-group mentoring, guided Qur’an reading with direct correction of pronunciation (makharij al-huruf) and tajwid, application of memorization and dictation (imla’) techniques, and varied teaching approaches through instructor rotation. Evaluation was conducted through pre-tests and post-tests, direct observation of students’ reading performance, and assessment of participation and attendance. The results indicate a significant improvement in students’ Qur’anic reading skills, particularly in fluency, accuracy of pronunciation, and basic understanding of tajwid. This program is expected to serve as a sustainable model for improving Qur’anic literacy in Qur’anic learning institutions.